SUSTAINABILITY OF WATER, SANITATION AND HEALTH PROJECTS IMPLEMENTED BY AFRICAN MEDICAL AND RESEARCH FOUNDATION IN NAIROBI CITY COUNTY, KENYA - Nabifwo, Lydia W.; Kimutai, Gladys (International Journal of Entrepreneurship and Project Management, 2018)
Purpose: Sustainability of community based and managed water sanitation and health projects in Kenya remains a challenge. This study sought to investigate the factors influencing sustainability of water sanitation and health projects implemented by AMREF in Nairobi County-Kenya. Methodology: A descriptive sample survey was used to describe the findings on water sanitation and health projects as they are on the ground without bias in selected households in Kibera slums in Nairobi County. A target population of 10,515 respondents was targeted. The researcher selected a sample of 433 from the target population using stratified random sampling. Data was collected by the use of a semi-structured questionnaire. The results were presented by using frequency tables and figures for ease of reference. The data was analysed using descriptive and inferential statistics. Results: The study found that that there is a significant positive influence of community participation, technical expertise, funds utilization and political factors on sustainability of water sanitation and health projects. Policy recommendations: The study therefore recommends that the policy makers should ensure that the policies are favourable to the private sectors to make them have the will to participate in the project. The study also recommends that all the staff should be frequently trained to acquire the right skill to enhance expertise in execution of responsibilities. The research suggests that the same studies should be conducted on the other parts of the country to enhance better sustainability of water sanitation and health projects in all parts of the country.